A study of morphological spectrum of testicular and paratesticular lesions - Dhanya K.; Anil Kumar Sirasagi (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Testis is affected by both neoplastic and non-neoplastic conditions which can present in all the age groups. Tumor-like proliferations from paratestis often mimic malignancy which results in unnecessary radical orchidectomy. Hence, one has to depend on histopathologic examination for definitive diagnosis. The testicular tumors although relatively rare, are of great interest and importance because of their varied histological appearances. They account for less than 1% of all malignancies in male. Non-neoplastic lesions or tumor-like proliferations from paratestis often mimic malignancy arising from the scrotal sac which results in unnecessary radical orchidectomy. Hydrocele is often associated with trauma and inguinal hernia, rarely it can be secondary to testicular cancer. Whereas pyocele is most often associated with epididymo-orchitis and less often from contiguous spread of bacterial peritonitis. Hence detailed history and pathological examination are required to know the underlying cause.Objective: To know the morphological spectrum of testicular and paratesticular lesions, their incidence in different age groups, laterality, incidence of benign versus malignant lesions and to study their gross, microscopic features. Methodology: This is a 2 years retrospective study from June 2017 to May 2019 at department of pathology, ESIC Medical college, Kalaburagi. Gross specimens, slides and blocks were retrieved and reviewed.Results: Total 49 cases were studied of which 26 were testicular lesions and 23 paratesticular lesions. Non neoplastic testicular lesions were more common than neoplastic lesions (96.1% Vs 3.8%) with majority in the fifth and sixth decade. Right testis was more commonly involved (59.09%) than left testis (31.8%) and bilateral involvement was seen in 9% cases. Atrophic testis was most common testicular lesion whereas Pyocele was most common paratesticular pathology.Conclusion: Testis and paratestis can develop both non neoplastic and neoplastic lesions. Gross morphology can give important clues for pathological diagnosis. However there is a crucial role of microscopic examination for definitive diagnosis of these lesions.